World on the brink : how America can beat China in the race for the twenty-first century - Alperovitch, Dmitri; Graff, Garrett M., 1981- (PublicAffairs, 2024)
"Over the past few decades, China has climbed the ranks of the global powers with staggering speed. Its vast economy and growing regional aggression make it a threat to supersede the United States as the world's dominant power. But this outcome is far from inevitable. Like neighboring Russia-which harbors global ambitions of its own-right now China is at a turning point. Whereas international sanctions and a turn away from fossil fuels are steadily smothering Russia, China's downfall will be its shrinking population. Its chance to achieve global hegemony will soon disappear, making its quest for power both less certain and more dangerous. In World on the Brink, security expert Dmitri Alperovitch breaks down not only the significant weaknesses that have so far prevented China from surpassing the United States, but also the key strategies that will enable the U. S. to maintain primacy even as China ramps up its efforts. Cultivating crucial alliances, fostering domestic innovation in emerging tech fields, and stabilizing international relations with adversarial nations are all vital components to building a robust strategy in anticipation of a new cold war that seems more likely every day. As Alperovitch explains, we must play to our strengths and address our weaknesses, using our leverage as the strongest nation on the planet to tactfully navigate the next cold war. This sharp, timely book is the essential blueprint for doing just that"--